2015
DOI: 10.1039/c5tc02356d
|View full text |Cite
|
Sign up to set email alerts
|

Sensitizers with rigidified-aromatics as the conjugated spacers for dye-sensitized solar cells

Abstract: Metal-free dye sensitized solar cells emerged as an important source of a renewable energy resource because of low production, simple fabrication process and a wide availablility of organic dyes. This review mainly focuses on metal-free sensitizers having rigidifed-aromatics as the conjugated spacer for applications in DSSCs. Based on their structures dyes have been divided into three major subsegments: (i) ladder type polyphenylenes with or without heteroatoms; (ii) rigidfied-aromatics as a donor segments; (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 110 publications
(40 citation statements)
references
References 104 publications
0
40
0
Order By: Relevance
“…2a, 9 On the basis of this concept, Eom et al reported the thieno[3,benzothiophene (TBT) moiety as a new πbridge in organic sensitizers (SGT-130, Figure 1), exhibiting a relatively good PCE of 10.47%. 2a, 9 On the basis of this concept, Eom et al reported the thieno[3,benzothiophene (TBT) moiety as a new πbridge in organic sensitizers (SGT-130, Figure 1), exhibiting a relatively good PCE of 10.47%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2a, 9 On the basis of this concept, Eom et al reported the thieno[3,benzothiophene (TBT) moiety as a new πbridge in organic sensitizers (SGT-130, Figure 1), exhibiting a relatively good PCE of 10.47%. 2a, 9 On the basis of this concept, Eom et al reported the thieno[3,benzothiophene (TBT) moiety as a new πbridge in organic sensitizers (SGT-130, Figure 1), exhibiting a relatively good PCE of 10.47%.…”
Section: Introductionmentioning
confidence: 99%
“…2a, 9 On the basis of this concept, Eom et al reported the thieno[3,benzothiophene (TBT) moiety as a new πbridge in organic sensitizers (SGT-130, Figure 1), exhibiting a relatively good PCE of 10.47%. The strategies to improve the π-bridge ability can be defined by: (i) extending the conjugation length of the πbridge, 9,13 (ii) substituting the bridging atom in a fused-ring π-bridge, 14 and (iii) increasing the electron-donating ability of the donor 15 . The strategies to improve the π-bridge ability can be defined by: (i) extending the conjugation length of the πbridge, 9,13 (ii) substituting the bridging atom in a fused-ring π-bridge, 14 and (iii) increasing the electron-donating ability of the donor 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Many chemists put their eyes on organic dyes because of their advantages such as low cost, low toxicity, easy structural modification and even efficiency predictable . Many kinds of excellent organic dyes have been developed, such as porphyrin dyes, N ‐annulated perylene dyes, and many different kinds of rigidified aromatics dyes . Dyes with D–π–A system is the main type organic dyes, which contains an electron donor (D), an electron acceptor (A), and a π‐conjugated spacer (π) to link the donor and acceptor .…”
Section: Methodsmentioning
confidence: 99%
“…Without the use of any coadsorbent, a sensitizer consisting of an N‐annulated indenoperylene donor and a secondary acceptor achieved a record efficiency of 12.5%, which surpassed the champion dye YD2‐o‐C8 8. Sensitizers with rigidified aromatic segments as the conjugated spacer were recently reviewed by us 37. Our first attempt to use a rigidified segment was the fluorene entity.…”
Section: Metal‐free Sensitizers For Dsscsmentioning
confidence: 99%